2016
DOI: 10.1021/acs.chemrestox.6b00143
|View full text |Cite|
|
Sign up to set email alerts
|

NADH:Cytochrome b5 Reductase and Cytochrome b5 Can Act as Sole Electron Donors to Human Cytochrome P450 1A1-Mediated Oxidation and DNA Adduct Formation by Benzo[a]pyrene

Abstract: Benzo[a]pyrene (BaP) is a human carcinogen that covalently binds to DNA after activation by cytochrome P450 (P450). Here, we investigated whether NADH:cytochrome b5 reductase (CBR) in the presence of cytochrome b5 can act as sole electron donor to human P450 1A1 during BaP oxidation and replace the canonical NADPH:cytochrome P450 reductase (POR) system. We also studied the efficiencies of the coenzymes of these reductases, NADPH as a coenzyme of POR, and NADH as a coenzyme of CBR, to mediate BaP oxidation. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 56 publications
7
44
0
Order By: Relevance
“…Recently, we have found that the NADH:cytochrome b 5 reductase/cytochrome b 5 /NADH system can also substitute the POR/NADPH system and act as an electron donor to another CYP enzyme, CYP1A1, for the oxidation of benzo[ a ]pyrene (BaP). This NADH-dependent system can, therefore, function as a sole electron donor for both reduction steps in the reaction cycles of CYP1A1 [ 39 , 40 ] and CYP3A4 [ 26 , 28 ]. Here, we investigated in detail, whether the NADH:cytochrome b 5 reductase/cytochrome b 5 /NADH system can also be the sole electron donor in the CYP3A4-catalyzed oxidation of ellipticine, Another aim of this work was to shed more light on the further functions of cytochrome b 5 in this CYP3A4-mediated reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have found that the NADH:cytochrome b 5 reductase/cytochrome b 5 /NADH system can also substitute the POR/NADPH system and act as an electron donor to another CYP enzyme, CYP1A1, for the oxidation of benzo[ a ]pyrene (BaP). This NADH-dependent system can, therefore, function as a sole electron donor for both reduction steps in the reaction cycles of CYP1A1 [ 39 , 40 ] and CYP3A4 [ 26 , 28 ]. Here, we investigated in detail, whether the NADH:cytochrome b 5 reductase/cytochrome b 5 /NADH system can also be the sole electron donor in the CYP3A4-catalyzed oxidation of ellipticine, Another aim of this work was to shed more light on the further functions of cytochrome b 5 in this CYP3A4-mediated reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum conditions obtained were pH 4.5, contact time of 20 h, and at concentration of 50 mg/mL, with the adsorption capacity of 85 mg/1x10 6 T. viride colonies. The proposed mechanism for biosorption is through adsorption of Pb(II) ions in the cell walls of T. viride, involving negatively charged functional groups in T. viride such as COO  , -, dan -NH  , and positive charged from metal ions.…”
Section: Resultsmentioning
confidence: 98%
“…It can be used efficiently for the treatment of large volumes of waste with low concentrations of pollutants. Thus, the process does not depend on the viability of biomass [6]. The application of microorganisms as biosorbents has several advantages due to their small size and the ability to adsorption, binding the concentrations of heavy metals from aqueous solutions including very dilute concentrations by certain types of inactive, dead and living microbes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals participate a vital function in tumor initiation by modification of cellular metabolic processes or direct chemical reaction. The stimulation of carcinogen is mainly catalyzed by phase I (CYP 450 and Cyt‐b 5 ) enzymes and detoxified by the presence of phase II (GST and GR) enzymes thereby protecting against carcinogenic injury . The scavengers of phase II enzymes represent of inhibitors at all stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%